Poétiques de l’altérité : lecture croisée de J.-H. Rosny aîné et Stanley G. Weinbaum - François Laforge (ReS Futurae, 2018)
This essay presents a cross-reading of two seminal works in early Science Fiction : Les Navigateurs de l’Infini by J. H. Rosny aîné, a novel published in 1925 and A Martian Odyssey by Stanley G. Weinbaum, a short story published in 1934. In spite of many differences between the two authors, especially regarding their positions in the literary fields they belonged to, both of them had the same concern to write high-level conjectural texts, plausible from a scientific point of view and intellectually stimulating. They also attempted to create totally different worlds in the aforementioned works and refused plain reduplicative imagination, unlike many previous or contemporary Science Fiction writers, such as Edgar Rice Burroughs or Gustave Le Rouge, who had both set adventure stories on Mars, at the beginning of the 20th Century. Rosny and Weinbaum also had in common a positive view of the Aliens they described, which was at odds with the paradigm prevalent in Science Fiction since The War of the Worlds by H. G. Wells. All those commonalities justify a comparative approach. Our reading will aim at providing some elements of reflection about the parallel history of American Science Fiction and so-called French Science Fiction before 1945. In our reading, we will wonder how consistent the worlds created by Weinbaum and Rosny are and what structural principles underlie them. We will also analyze the way the two authors dealt with the question of communication with Aliens, which is pivotal to modern Science Fiction. At last, we will try to define the ideological backgrounds of those texts, which can be both read as utopias, a metaphysical one in Rosny’s novel and a political one in Weinbaum’s short story.